Positioning the Tata Nano (B) - Tybout, Alice M.; Fahey, Natalie ([London] : SAGE, 2016)
The case focuses on positioning a new brand, the Tata Nano. The car has been widely publicized as the world's cheapest car at Rs.1 lakh. Students must consider the gap between the ultimate target, the huge emerging middle class of Indian consumers, and the limited capacity and distribution available in choosing a target. They also must select between alternative competitive frames and the various points of difference they highlight. The case unfolds in two stages. The first decision point is in 2009, at the time of the product launch. The second decision point is 18 months later, after production capacity has increased and some product safety issues have arisen.
Originally Published in: Tybout, A. M., & Fahey, N. (2011). Positioning the Tata Nano (B) (teaching notes revised 16/01/2013). 5-311-506(B). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Tata Motors; Marketing -- Case studies; Nano automobile -- Marketing -- Case studies